Post-treatment with glycyrrhizin can attenuate hepatic mitochondrial damage induced by acetaminophen in mice. Issue 10 (May 2021) - Dang, Xue-Liang; Yang, Long-Fei; Shi, Lei; Li, Long-Fei; He, Ping; Chen, Jie; Zheng, Bei-Jie; Yang, Peng; Wen, Ai-Dong
Overdose of acetaminophen (APAP) is responsible for the most cases of acute liver failure worldwide. Hepatic mitochondrial damage mediated by neuronal nitric oxide synthase- (nNOS) induced liver protein tyrosine nitration plays a critical role in the pathophysiology of APAP hepatotoxicity. It has been reported that pre-treatment or co-treatment with glycyrrhizin can protect against hepatotoxicity through prevention of hepatocellular apoptosis. However, the majority of APAP-induced acute liver failure cases are people intentionally taking the drug to commit suicide. Any preventive treatment is of little value in practice. In addition, the hepatocellular damage induced by APAP is considered to be oncotic necrosis rather than apoptosis. In the present study, our aim is to investigate if glycyrrhizin can be used therapeutically and the underlying mechanisms of APAP hepatotoxicity protection. Hepatic damage was induced by 300 mg/kg APAP in balb/c mice, followed with administration of 40, 80, or 160 mg/kg glycyrrhizin 90 min later. Mice were euthanized and harvested at 6 h post-APAP. Compared with model controls, glycyrrhizin post-treatment attenuated hepatic mitochondrial and hepatocellular damages, as indicated by decreased serum glutamate dehydrogenase, alanine aminotransferase, and aspartate aminotransferase activities as well as ameliorated mitochondrial swollen, distortion, and hepatocellular necrosis. Notably, 80 mg/kg glycyrrhizin inhibited hepatic nNOS activity and its mRNA and protein expression levels by 16.9, 14.9, and 28.3%, respectively. These results were consistent with the decreased liver nitric oxide content and liver protein tyrosine nitration indicated by 3-nitrotyrosine staining. Moreover, glycyrrhizin did not affect the APAP metabolic activation, and the survival rate of ALF mice was increased by glycyrrhizin. The present study indicates that post-treatment with glycyrrhizin can dose-dependently attenuate hepatic mitochondrial damage and inhibit the up-regulation of hepatic nNOS induced by APAP. Glycyrrhizin shows promise as drug for the treatment of APAP hepatotoxicity.